Virtual World and Freedom: Information, Genome and Depoliticization - Cataldo-Gonzalez, H (CENTRO ALTOS ESTUDIOS FILOSOFICOS & CIENCIAS SOCIALES-CENALTES, 2020)
The article analyzes the information on the Internet of Things, based on Evgeny Morozov s approach, and in genome studies, on Paula Sibilia s approach, identifying the main characteristics of the information, critically and reflexively relating them to the freedom that is derived from it, mainly, in its link with the market, surveillance and control, and with the disembodiment and depoliticization inherent in it.